(untitled) (Environment & Health, 2017)
Objective: We studied quantitative and qualitative indicators of rheoencephalography in the individuals with acoutrauma obtained in a zone of the antiterrorist operation (ATO). Materials and methods: We performed a rheoencephalography of 50 patients with acoutrauma obtained in a zone of the ATO. 15 healthy normal hearing individuals were a control. For the study of cerebral circulation we performed the rheoencephalography with the help of the computer rheograph of the company "DX-systems" (Ukraine). Results: At the qualitative assessment of the rheograms of the examined patients we revealed the circulatory disorders of the brain both in carotid (FM) and vertebral-basilar (OM) systems. According to the REG the normal indicators of the cerebral circulation state were not registered in any patient with acoutrauma. We observed an increase of the tonus of cerebral vessels with angiospasm effects only among 4% of the examined soldiers. There was a difficulty of venous outflow in 90.0 % of the cases in carotid system and in100.0% in vertebral-basilar one. Among the examined patients we also often registered a decrease of the tonus of cerebral vessels (30.0 %) and even the cases of atonic curve (22.0 %). There was a significant part of the patients with an unstable vascular tonus with a tendency to its increase (8.0 %) or to a decrease (58.0 %) in both systems of cerebral circulation. As to a pulse blood filling, there was a decrease in the carotid system in 66.0 % of the cases and in 84% in the vertebral-basilar pool among the patients with acoutrauma. An asymmetry of the REG curves (8.0 %) was also noted in the vertebral-basilar system of the ATO soldiers. Analysis of the quantitative REG indicators in the individuals of the studied groups in comparison to the control group (K) showed the significant (P